Policy and practice of checking vaccination status at school in 2018, a global overview. Issue 16 (6th April 2022) - Sadigh, Katrin; Fox, Garrett; Khetsuriani, Nino; Gao, Hongjiang; Shendale, Stephanie; Ward, Kirsten
Highlights: Checking vaccination status at school was reported by 77% of the countries in 2018 Individual home-based records were the most frequently checked document Children were most often referred to health centers to receive missed vaccines Checking vaccination status at school was infrequently monitored or evaluated Abstract: Background: Checking vaccination status at school is widely recommended as a strategy to strengthen routine childhood vaccination coverage. Documentation of approaches, challenges, strengths, and impact of this strategy in a variety of contexts is key to enhancing adoption and implementation. However, there is limited information about the prevalence of policies and the implementation of checking vaccination status at school globally. Methods: A one-time supplementary survey was circulated with the annual World Health Organization (WHO) and United Nations International Children's Emergency Fund (UNICEF) Joint Reporting Form in 2019 to all WHO member states and non-member state reporting entities. Additional publicly available country-level data, including primary school enrollment, home-based record (HBR) ownership, and World Bank income classification were linked to the supplementary survey responses, which were descriptively analyzed. Results: We received survey responses from 130 of the 194 (67%) WHO member states and 15 non-member state reporting entities. Almost half (46%) of the respondents reported having a law requiring proof of vaccination to enter at least one level of education, and 60% of the respondents reported having a law that requires checking vaccination status at school in 2018. Three-quarters of the respondents (77%) reported the practice of routinely checking vaccination status at school. Both laws and the practice of checking were more common in the WHO Region of the Americas and the WHO European Region, and in high- and upper-middle-income countries. Individual HBR was the document most frequently checked. Catch-up vaccination occurred most frequently at health centers. Evaluation of checking vaccination status at school to determine what has worked and its effect was infrequently reported. Conclusion: Despite widespread implementation of checking vaccination status at school in 2018, documentation of the experiences in planning and implementing this strategy, and its effects remains sparse, particularly in low- and middle-income countries.